Red Ginger Reduced Pain Due to Primary Dysminorrhoea in Adolescent Girls - Hidayati, Ulfa Nur; Susanti, Nanik; Winarsih, Lilik; Wardani, Arti; Fithri, An Nisa (Jurnal Kesmas Prima Indonesia, 2025)
Primary dysmenorrhea is common among adolescent girls and affects their quality of life and daily activities. Therefore,effective and safe treatments are needed. This study aims to evaluate the effectiveness of red ginger consumption in reducing the intensity of primary dysmenorrhea pain in adolescent girls. The research design used was a pre-experimental design with a one-group pretest-posttest design. The study was conducted at SMK "P" Batu City from September to December 2024, involving 32 adolescent female participants selected through a total sampling technique. The independent variable was the consumption of red ginger, 200 ml, twice daily (morning and evening), and the dependent variable was the intensity of dysmenorrhea pain. Pain levels were measured before and after the intervention using direct observation instruments. Data analysis was performed by calculating the frequency distribution and the Wilcoxon statistical test. The results showed that before the intervention, most respondents experienced moderate pain (59.4%) and severe pain (21.9%). After red ginger consumption, there was a significant decrease in pain intensity. On the first day of intervention, 68.6% had mild pain, and 25% had moderate pain. On the second day, 46.8% reported no pain, and 40.6% experienced only mild pain. Wilcoxon test results revealed a significant difference in pain intensity between the pre-intervention and post-intervention periods (p < 0.001). Thus, red ginger consumption is proven to be significantly effective in reducing primary dysmenorrhea pain intensity in adolescent girls.